EFISIENSI WAKTU TUNGGU PENDAFTARAN ONLINE PASIEN RAWAT JALAN : LITERATURE REVIEW - Asih Prasetyowati (STIKES HAKLI Semarang, 2021)
Abstract The online outpatient registration system is designed to provide benefits for the convenience of patients, reducing queues and increasing the efficiency of registration waiting times. The purpose of this study was to determine the flow, the application, and the efficiency of waiting time for online outpatient registration. The study used a literature review method with a qualitative approach. The literature search begins with topic selection for article searches through the googlescholar database, after which the data is filtered using inclusion and exclusion. Data was extracted and synthesized using narrative method. The online outpatient registration flow is the stage used by patients in registering outpatients without coming to the hospital first. Online outpatient registration systems are generally in the form of websites, smartphones, SMS, and whatsapp. Each online outpatient registration system has its own advantages and disadvantages. The online outpatient registration system provides benefits for patients in the form of getting a queue number, certainty of treatment time and information about services. The online outpatient registration system is more efficient than the in-person registration system. Hospitals can use more than one online outpatient registration application for alternative that suits patient needs. Keywords: efficiency, waiting time, online outpatient registration. Abstrak Sistem pendaftaran rawat jalan online dirancang untuk memberikan manfaat bagi kemudahan pasien, mengurangi antrian dan meningkatkan efisiensi waktu tunggu pendaftaran. Tujuan penelitian ini adalah mengetahui alur, aplikasi, dan efisiensi waktu tunggu pendaftaran rawat jalan online. Penelitian menggunakan metode literature review dengan pendekatan kualitatif. Pencarian literatur diawali dengan pemilihan topik, kemudian ditentukan keyword untuk pencarian artikel melalui database googlescholar, setelah itu data disaring menggunakan inklusi dan eksklusi, kemudian data diekstraksi dan disintesis dengan metode naratif. Alur pendaftaran rawat jalan online adalah tahapan yang digunakan oleh pasien dalam mendaftar rawat jalan tanpa datang ke rumah sakit terlebih dahulu. Sistem pendaftaran rawat jalan online umumnya berupa website, smartphone, SMS dan whatsapp. Setiap sistem pendaftaran rawat jalan online memiliki kelebihan dan kekurangan masing-masing. Sistem pendaftaran rawat jalan online memberikan keuntungan bagi pasien berupa mendapatkan nomor antrian, kepastian waktu berobat, dan informasi mengenai pelayanan. Sistem pendaftaran rawat jalan online lebih efisien daripada sistem pendaftaran datang langsung. Rumah sakit dapat menggunakan lebih dari satu aplikasi pendaftaran rawat jalan online sehingga pasien dapat memilih alternatif sesuai kebutuhan. Kata kunci : efisiensi, waktu tunggu, pendaftaran rawat jalan online